Camouflagic presentation of a shwannoma as an anterior mediastinal mass with significant airway collapse -a case report - Pathak, Soumi; Chowdhury, Itee; Bhargava, Ajay Kumar (Journal of Society of Anesthesiologists of Nepal, 2016)
The anaesthetic management of diagnostic and surgical procedure in patients with anterior mediastinal mass presents life-threatening challenges. This is usually caused by extrinsic compression of the airway, obstruction to the venous return or cardiac output. Common symptoms of cardio respiratory compression are positional dyspnoea, orthopnoea, stridor, syncope, and superior venacaval syndrome. A previously asymptomatic person may develop catastrophic airway collapse or cardiovascular compromise under anaesthesia hence careful evaluation and discussion between a multidisciplinary team is essential. We report management of a case of shwannoma presenting as anterior mediastinal mass resulting in collapse of upper one third of trachea with twenty percentage luminal opening. The purpose of our reporting is to emphasise that patients with significant tracheomalacia and eighty percentage decreased tracheal lumen may be asymptomatic, thus a thorough evaluation and skeptical vigilance and pre-emptive thinking is required to deal with the challenges posed by them. The use of endobronchial ultrasound, impulse oscillometry and negative expiratory pressure tests may be valuable for assessing the cause of the central airway collapse and for further management of these patients.